2014
DOI: 10.5530/jyp.2014.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-epileptic drug utilization and treatment outcome among epileptic patients on follow-up in a resource poor setting

Abstract: Introduction: Anti-epileptic drugs (AEDs) are the primary therapeutic modes for epileptic patients and have been demonstrated to control seizure, which decreases morbidity and mortality associated with epilepsy. There is a paucity of data on treatment outcome among epileptic patients in resource poor settings. The aim of this study was to assess AED utilization pattern and treatment outcome among epileptic patients on follow-up. Materials and Methods: A retrospective cross-sectional study was conducted among e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 12 publications
3
32
4
Order By: Relevance
“…In this study, the most commonly prescribed AED as monotherapy was phenobarbitone (81.8%) followed by phenytoin (15.4%). is is in line with the studies conducted in Jimma and Gonder, Ethiopia [17,18]. In contrast to this, a study done in the United Kingdom reported that the most commonly used AED was carbamazepine (37.4%) followed by sodium valproate (35.7%) [19].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the most commonly prescribed AED as monotherapy was phenobarbitone (81.8%) followed by phenytoin (15.4%). is is in line with the studies conducted in Jimma and Gonder, Ethiopia [17,18]. In contrast to this, a study done in the United Kingdom reported that the most commonly used AED was carbamazepine (37.4%) followed by sodium valproate (35.7%) [19].…”
Section: Discussionsupporting
confidence: 86%
“…Another study in Bisho u general hospital also reported monotherapy users to be 78.6% [26] and a study done by Birru et al also found that 80.35% [27] of studied patients used single drug for treatment of their epilepsy. However Gurshaw et al reported only 54.5% of studied epileptic patients in Jimma university hospital used monotherapy [28].…”
Section: Discussionmentioning
confidence: 99%
“…Choice of the most appropriate AEDs depends on proper classification of seizures type. Lack of proper seizure classification affects AEDs selection and treatment outcome [22,23]. About 8% of the study participants had uncategorized seizure type, which could possibly have contributed to inappropriate drug selection and poor treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%